Elucidation of B-cell specific drug immunogenicity liabilities via a novel ex vivo assay - Looney, Cary M.; Ducret, Axel; Steiner, Guido; Dernick, Karen; Hartman, Katharina; Siegel, Michel; Hickling, Timothy; Odermatt, Alex; Marban-Doran, Céline (Frontiers in Immunology, 2025)
The advent of large molecule therapeutics has revolutionized treatment options for previously unmet medical needs. This advent has also led to an increased impact of immunogenicity on drug efficacy and safety. In order to maximize the potential of large molecule therapeutics, immunogenicity-related liabilities must be identified as early in development as possible, using an integrated risk assessment that takes into account the various cell types and processes involved. Here, we describe the development of an ex vivo B-cell immunogenicity assay, to capture a key component of the immune response that has been missing from previously published ex vivo immunogenicity assays. Plasmablasts/plasma cells were preferentially expanded in this assay, a subset of which were drug-specific and presented drug-specific peptides on MHC Class II. This assay represents an important tool in the immunogenicity risk assessment toolkit, to allow liabilities to be identified and mitigated early in the drug development process.